2014
DOI: 10.1155/2014/327537
|View full text |Cite
|
Sign up to set email alerts
|

Lobe-Specific Heterogeneity in Asymmetric Dimethylarginine and Matrix Metalloproteinase Levels in a Rat Model of Obstructive Cholestasis

Abstract: We investigated the effects of obstructive cholestasis in different hepatic lobes by evaluating asymmetric dimethylarginine (ADMA) (a nitric oxide synthase inhibitor), protein methyltransferase (PRMT) and dimethylarginine dimethylaminohydrolase (DDAH) (enzymes involved, resp., in its synthesis and degradation), the cationic transporter (CAT), and metalloproteinase (MMP) activity. Sixteen male Wistar rats underwent a 3-day cholestasis by common bile duct ligation (BDL) or sham operation. Blood samples and hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…The relative increase in fibrosis in the RL than in the LL may be one of the causes of more markedly impaired regenerative capacity of the RL than LL [10]. These results are in line with our previous studies using both control rats and other models of liver disease such as cholestasis and ischemia/reperfusion (I/R) damage: MMP activity was particularly high in the RL as compared with the ML and LL [12, 13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The relative increase in fibrosis in the RL than in the LL may be one of the causes of more markedly impaired regenerative capacity of the RL than LL [10]. These results are in line with our previous studies using both control rats and other models of liver disease such as cholestasis and ischemia/reperfusion (I/R) damage: MMP activity was particularly high in the RL as compared with the ML and LL [12, 13].…”
Section: Discussionsupporting
confidence: 87%
“…Many differences between liver lobes are found in several hepatic diseases and toxic injury such as chemical carcinogenesis, cirrhosis, and acetaminophen toxicity [911]. We previously demonstrated that a functional lobar heterogeneity of the liver exists in ischemia/reperfusion and obstructive cholestasis animal models, indicating that different events such as modulation of the extracellular matrix (ECM) and oxidative stress occur with different intensities in the hepatic lobes [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic MMPs were extracted by homogenization (IKA-ULTRA TURRAX T10) of frozen liver tissue. Protein extraction from snap-frozen liver tissue, bile and serum and gelatin zymography were performed as described previously [ 20 ]. Briefly, the homogenate sample protein content was normalized by a final concentration of 400 μg/mL in the sample loading buffer (0.25 M Tris-HCl, 4% sucrose w/v, 10% SDS w/v, and 0.1% bromophenol blue w/v, pH 6.8).…”
Section: Methodsmentioning
confidence: 99%
“…The BDL rats exhibited a decreased rate of ADMA removal of about 50% , suggesting that the impossibility of bile excretion induces an increase in circulating ADMA. Additionally, we reported that a short BDL period induced a significant increase in tissue ADMA . Moreover, an increase in the plasma concentration of ADMA has also been found in human alcoholic cirrhosis only when high levels of plasma bilirubin have also been found, suggesting a correlation between compromised biliary excretion of bilirubin and increase in ADMA plasma .…”
Section: Discussionmentioning
confidence: 70%